Biosimilars in India; current status and future perspectives - Bikash R Meher; Sakthi Balan; Rashmi R Mohanty; Monalisa Jena; Smita Das (Wolters Kluwer Medknow Publications, 2019)
Many key biologics are scheduled to lose their patent by the year 2020, which will provide the opportunity to other biopharmaceutical companies to develop the similar biologics. Biosimilar or similar biologic used has increased in the recent year following the approval of the first biosimilar in early 2000. India is one of the leading manufacturers of similar biologics. India has developed a new guideline in 2012 for the pre- and post-marketing approval of similar biologics.